Acceleration of ultra-high-energy cosmic rays in the kiloparsec-scale jets of nearby radio galaxies - Wang, Jie-Shuang; Reville, Brian; Rieger, Frank M.; Aharonian, Felix A. (The astrophysical journal. Part 2, Letters, 2024)
Radio galaxies have long been considered as potential sources of ultra-high-energy cosmic rays (UHECRs). Recent analyses of the UHECR spectrum, composition, and arrival directions indicate that the nearest radio galaxy, Centaurus A, could be linked to the reported dipole anisotropy, though the mechanism underlying the acceleration remains elusive. In this Letter, we explore UHECR acceleration in the kiloparsec-scale jets of radio galaxies, exemplified by Centaurus A. Using high-resolution relativistic magnetohydrodynamic and test-particle simulations without subgrid physics, we investigate the acceleration of the highest-energy particles in the turbulent sheath of a fast-moving jet. Our findings demonstrate that acceleration close to the maximum theoretical expectation is possible. When extrapolated to nearby radio galaxies, our results suggest that the kiloparsec-scale jets of Centaurus A could account for the dipole anisotropy in UHECRs, while more potent Fanaroff-Riley type II radio galaxies may account for the observed UHECR spectrum with a rigidity cutoff at a few Exavolts.